Strong metal-support interaction effect of Pt/Nb2O5 catalysts on aqueous phase hydrodeoxygenation of 1,6-hexanediol - Jun, Jin-Woo; Suh, Young-Woong; Suh, Dong Jin; Lee, Yong-Kul (ELSEVIER SCIENCE BV, 2018)
A series of Pt/Nb2O5 catalysts were synthesized at different temperature conditions to investigate metal-support interaction effect on the catalytic activities in the aqueous phase hydrodeoxygenation of 1,6-hexanediol at 523 K and 5.5 MPa. The increase of calcination temperature of Nb2O5 support over 773 K lowered surface area as well as acidity of Nb2O5, which altered the electron density of the active center Pt as characterized by XANES analysis. It was demonstrated that the bifunctional catalytic nature of Pt/Nb2O5 catalyst having high acidity and electron deficiency could promote the dehydration of 1,6-hexanediol followed by hydrogenation with high selectivity toward n-hexane.
Keywords: ACID CATALYSTS; PYROLYSIS OIL; FATTY-ACIDS; BIOMASS; DEHYDRATION; GUAIACOL; GLYCEROL; ALKANES; TRIGLYCERIDES; INDICATORS